Bangkit Kenari Enterprise web based ordering system / Fatin Nur Izzati Rameli - Rameli, Fatin Nur Izzati (2013)
The research project was conducted to show the usage of electronic commerce application among small-medium enterprise, SMEs, in Malaysia by focusing on Bangkit Kenari Enterprise, which is located in Kedah. A survey and interview have been conducted to collect all the data regarding the ordering process that was being used by the company. A web based ordering system was created to overcome the problem of the company in handling the ordering system. Using the rapid prototyping method, the research project focused on seven phases to solve the current problems that being faced by the company and demonstrate the usefulness towards the adoption of electronic commerce by SMEs. At the same time, by the implementation of electronic commerce, the company will able to cope with the changes, speeding up the business decision, hence able to compete with other SMEs in Malaysia. The research project indicated that the application of web based ordering system for Bangkit Kenari Enterprise were significant towards enhancing the application of electronic commerce by SMEs and thus maintaining the company competitive advantage in the Malaysia’s industry